Evaluation of NMR structural studies on a family of membrane active channel forming peptides - Herrera, Alvaro Ivan (Kansas State University, 2015)
As part of the ongoing development of a channel forming peptide with the potential to be used clinically to treat cystic fibrosis, a number of structural studies using solution NMR spectroscopy have been carried out on a number of the test sequences. Given their structural similarities of the monomers it is important to evaluate whether or not there is a compelling need to determine the solution NMR structure of next-generation peptides. The determination of the NMR monomeric solution structure of peptides NK₄-M2GlyR-p22 and NK₄-M2GlyR-p20 T17R S20W in TFE solution and SDS micelles sample shows predominantly alpha-helical conformations for both sequences with an extended conformation for the N-terminal lysine residues. The I[subscript max], K[subscript 1/2] and Hill coefficient, derived from data on ion conductance across monolayers of MDCK cells, were used to compare the ion conductance properties of the peptide sequences. Peptide NK₄ M2GlyR p20 T17R S20W has both a higher I[subscript MAX] (43.8 ± 2.8 μA/cm²) and a lower K[subscript 1/2] (58 ± 8 μM) compared to other M2GlyR derived peptides with calculated NMR structures. All available molecular structures calculated by NMR for M2GlyR derived peptides were compared and the correlation of the structural changes observed in the NMR structures with the ion conductance changes was evaluated. The NMR structures were found to have limited predicting potential over the ion conduction data. NMR determined structures have provided an experimentally based starting point for studies of the channels formed by the family of M2GlyR peptides. Computer simulations account for inter peptide interactions and packing effects that are not experienced by the monomeric form of the peptides in the NMR samples that have been used until now. The determination of the structure of the oligomeric peptide channels is deemed needed to improve the relevance of future use of NMR in this project. The use of larger membrane mimicking agents, isotopically labeled (¹⁵N, ¹³C) samples, 3D NMR experiments and potentially solid state NMR would be required to accomplish that task.
Keywords: Nuclear magnetic resonance; Peptide; Channel; Cystic fibrosis; Ion conductance; Biochemistry (0487); Biophysics (0786)